Foreign body perforation acute abdomen in Meckel's diverticulum - Mouchrek, Benedito Dario Murad; Santos, Rennan Abud Pinheiro; Rocha, Marcelo Lima; Santos, Orlando José dos; Mesquita, Lucas Marques de; Araújo, Eduardo Medeiros de; Morais, Adriana Oliveira Dias de Sousa (Seven Editora, 2024)
The present report describes an incidental finding of Meckel's diverticulum due to fish spine drilling in a 28-year-old male patient, where the technique used was videolaparoscopic diverticulectomy with an endoscope clamper, and the removal of the foreign body successfully in the treatment, guaranteeing a good post-operative recovery. DOI:https://doi.org/10.56238/sevened2024.001-021